Risk of osteoporosis in endocrine disorders and celiac disease - VELIA STAZI, Anna; TRINTI, Biagino (Annali dell'Istituto superiore di sanita, 2007)
Osteoporosis is characterized by a loss of bone mass; the bones become less dense, fragile and prone to fracturing. It is regulated by endocrine-environmental factors with the genetic component accounting for 70% of an individual's variation in bone mass density (BMD). Pathological conditions such as celiac disease (CD) exacerbate the process of bone loss and the presence of osteoporosis in celiac subjects may be the only sign of undiagnosed CD. The interleukins IL-1alpha and IL-1beta are stimulators of bone resorption; the relatives of celiac patients shown the increased IL-1beta supporting the genetic susceptibility. In women osteoporosis is indirectly associated with early menopause and amenorrhea, while in men it is associated with hypogonadism and GH deficit. The direct effect on the bones of CD is secondary to poor absorption of calcium and vitamin D. These endocrine and non-endocrine factors exert their effects on bones by modulating the RANK/RANK-L/OPG system.